Sonocrystallization for Optimized Chemical Mechanical Planarization (CMP) in Semiconductor Fabrication - Chintala, Suman (Journal of Research in Science and Engineering, 2025)
Sonocrystallization, a process that uses sound waves to control the formation and growth of crystals, is gaining attention in the chemical mechanical planarization (CMP) process for semiconductor manufacturing. CMP is a polishing technique used to smooth and flatten the surfaces of wafers during chip production. One of the main challenges in CMP is the need for high-performance polishing slurries—liquid mixtures that contain abrasive particles and chemicals. The size and uniformity of these particles are critical, as they directly impact how evenly the wafer is polished and how well it performs. Sonocrystallization offers a unique solution by using ultrasound to produce particles with highly uniform sizes. This improves the polishing efficiency and reduces defects on the wafer surface, leading to more reliable chips. Additionally, the technique allows for better control over slurry composition, making it easier to tailor slurries for advanced semiconductor materials, such as those used in 3D chips or next-generation transistors. As semiconductor devices become smaller and more complex, sonocrystallization in CMP slurries is emerging as a promising innovation to meet the industry's high standards for precision and performance.